2021
DOI: 10.1002/anie.202107731
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Metal Defect and Surface Chemical Reconstruction into NiCo2S4/ZnS Heterojunction to Achieve Outstanding Oxygen Evolution Performance

Abstract: Defect and interface engineering are recognized as effective strategies to regulate electronic structure and improve activity of metal sulfide. However, the practical application of sulfide is restricted by their low conductivity and rapid decline in activity derived from large volume fluctuation during electrocatalysis process. More importantly, the determination of exact active site of sulfide is complicated due to the inevitable electrochemical reconstruction. Herein, ZnS nanoparticles with Zn defect are an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
98
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(108 citation statements)
references
References 38 publications
(33 reference statements)
4
98
0
Order By: Relevance
“…The reversibility and the bifunctional catalytic activity of the oxygen electrodes are usually calculated from the potential difference between the OER current density at 10 mA/cm 2 ( E j10,OER ) and the half‐wave potential ( E 1/2,ORR ) of the ORR current density (Table S3) according to the equation: ΔE = E j10,OER – E 1/2,ORR . For a better bifunctional catalytic activity of a catalyst, ΔE should be smaller and thus, it becomes more promising for practical applications, as compared with some reported literature values (Table S4) [63,66] . Among the as‐prepared catalysts, VS 2 /rGO demonstrates the smallest ΔE value of 0.75 V. The overall result demonstrates that rGO significantly enhances the bifunctional ORR/OER activity of VS 2 thereby, promoting the adsorption of oxygenated intermediates on both VS 2 and rGO surfaces.…”
Section: Resultsmentioning
confidence: 94%
“…The reversibility and the bifunctional catalytic activity of the oxygen electrodes are usually calculated from the potential difference between the OER current density at 10 mA/cm 2 ( E j10,OER ) and the half‐wave potential ( E 1/2,ORR ) of the ORR current density (Table S3) according to the equation: ΔE = E j10,OER – E 1/2,ORR . For a better bifunctional catalytic activity of a catalyst, ΔE should be smaller and thus, it becomes more promising for practical applications, as compared with some reported literature values (Table S4) [63,66] . Among the as‐prepared catalysts, VS 2 /rGO demonstrates the smallest ΔE value of 0.75 V. The overall result demonstrates that rGO significantly enhances the bifunctional ORR/OER activity of VS 2 thereby, promoting the adsorption of oxygenated intermediates on both VS 2 and rGO surfaces.…”
Section: Resultsmentioning
confidence: 94%
“…This also underscores the electronic integration of cocatalyst with TiO 2 , which is supported by different spectral and microscopy analysis and could be the reason for the enhanced activity. It is also worth mentioning the synergy effect between the surface structure of Pd and Pt for better HCHO activity rather than the metal–support (TiO 2 ) interaction; while the former decides the overpotential of the redox reaction, the latter decides the metal–semiconductor junction and hence electron–hole pair separation/diffusion. As indicated earlier, the (111) surface facets of Pd TO lead to a similar structure with deposited Pt, which exhibits higher oxidation activity.…”
Section: Resultsmentioning
confidence: 99%
“…Reports are also available on the core–shell catalysts for different applications such as catalytic, electrocatalytic, and photocatalytic reactions. ,, For instance, Bai et al, reported the tuning of Pt shell thickness over a Pd core, and it is possible to produce highly active and stable cocatalysts with titania for photocatalytic hydrogen generation due to enhanced charge separation features . In fact, it is well established in the literature that the synergetic effects of various components has been demonstrated for improved performance of various catalytic reactions. Particular attention is paid to understand the changes in surface properties and its correlation to the photocatalytic results observed in the present work.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the problems discussed above, nonprecious-metal-based catalysts with acceptable price, benign activity, and superior stability have been widely studied during the past decades. Transition-metal-based (oxy)­hydroxides might be an alternative to precious-metal-based catalysts in alkaline media due to their tunable electronic properties, earth-abundant resources, and easy synthesis routes. Tuning the electronic structures by doping or creating vacancies to meet the smallest free energy for *OH and *OOH is an efficient way to lower the overpotential of the OER. In this sense, nickel- and cobalt-based hydroxides are widely studied because of their high catalytic activity and adjustable electronic structure. , For example, Qiu et al doped NiO with Fe and found that the overpotential at 10 mA/cm 2 for Fe–NiO/NF was only 305 mV .…”
Section: Introductionmentioning
confidence: 99%